Shoreline Changes in The Coastal Areas of Kendal Regency, Semarang City, and Demak Regency 1996-2024 - Falah, Jhonata; Muta’ali, Luthfi; Saputra, Erlis (JURNAL PESISIR DAN LAUT TROPIS, 2026)
The coastal regions of Kendal Regency, Semarang City, and Demak Regency are strategic areas experiencing significant environmental dynamics, particularly regarding shoreline shifts and land-use changes. These transformations are driven by a combination of natural factors—such as waves, currents, tides, and sedimentation—and anthropogenic factors, including land subsidence, infrastructure development, reclamation, and land-use conversion. This study aims to identify shoreline changes between 1996 and 2024. Using a quantitative descriptive method, the research utilized multitemporal satellite imagery from Landsat 5,7, and 8 year 1996-2024. Shoreline extraction was performed using the Normalized Difference Water Index (NDWI), while change analysis was conducted through the Digital Shoreline Analysis System (DSAS) using Net Shoreline Movement (NSM) and Linear Regression Rate (LRR) parameters. The results indicate that the majority of the study area experienced accretion, with an average change rate of 9,08 m/year. Accretion accounted for 45.84% of the shoreline, followed by erosion (38.34%), stable conditions (2.67%), and reclamation (13.15%). The highest accretion was observed in Wedung District (Demak Regency), the most significant erosion in Sayung District (Demak Regency), stable conditions in Rowosari District (Kendal Regency), and the most extensive reclamation in Tugu District (Semarang City). These findings serve as a reference for Spatial Planning in Jawa Tengah. Keywords: shoreline change, coastal, DSAS Abstrak Wilayah pesisir Kabupaten Kendal, Kota Semarang, dan Kabupaten Demak merupakan kawasan strategis yang mengalami dinamika lingkungan sangat tinggi, khususnya terkait perubahan garis pantai dan penggunaan lahan. Perubahan tersebut dipengaruhi oleh kombinasi faktor alami seperti gelombang, arus, pasang surut, dan sedimentasi, serta faktor antropogenik seperti penurunan muka tanah, pembangunan infrastruktur, reklamasi, dan konversi penggunaan lahan. Penelitian ini bertujuan untuk mengidentifikasi perubahan garis pantai tahun 1996–2024. Metode penelitian yang digunakan yakni deskriptif kuantitatif dengan memanfaatkan data sekunder berupa citra satelit multitemporal berupa Landsat 5,7 dan 8 tahun 1996-2024. Untuk ekstraksi garis pantai dari citra menggunakan teknik Normalized Difference Water Index (NDWI), sedangkan perubahan garis pantai menggunakan teknik Digital Shoreline Analysis System (DSAS) dengan parameter Net Shoreline Movement (NSM) dan Linear Regression Rate (LRR). Hasil penelitian menunjukkan bahwa sebagian besar mengalami akresi dengan rata-rata laju perubahan sebesar 9,08 m/tahun dengan persentase kondisi akresi (45,84%,), disusul abrasi (38,34%,), kondisi tetap (2,67%,), dan reklamasi (13,15%.). Pada kondisi akresi tertinggi berada di Kecamatan Wedung Kabupaten Demak, kondisi abrasi tertinggi berada di Kecamatan Sayung Kabupaten Demak, kondisi tetap pada Kecamatan Rowosari Kabupaten Kendal, sedangkan reklamasi tertinggi terjadi di Kecamatan Tugu Kota Semarang. hasil penelitian ini dapat menjadi referensi dalam Rencana Tata Ruang di Jawa Tengah. Kata kunci: perubahan garis pantai, pesisir, DSAS